A review of major industrial accidents in Malaysia: article - Mohd Nasir, Nafiz Syadhamier; Jafri, Hasnora (2017)
The occurrence of industrial accidents in Malaysia are increased in parallel to the growth of the industries. Industrial accidents occur for a number of reasons. It may results in major injuries or even in some cases, death. The main objective of this study is to review of the past industrial accidents in Malaysia. This is done by defining the meaning of industrial accidents and analyzing the causes and the types of the accidents. The data from Department of Occupational Safety and Health (DOSH) and Social Security Organization (SOCSO) were collected and were examined on the frequencies of the industrial accidents in Malaysia. Statistics reported by the National Institute of Occupational Safety and Health (NIOSH) and Construction Industry Development Board (CIDB) were also been reviewed. The findings of this study showed that majority of the accident cases reported in Malaysia are industrial accidents. This numbers came from all sectors of the industries. Existing records indicated that the present accidents rate in the industry is still very much adverse and below expectation. This paper further examined the relationship between the accidents rate in Malaysia with those in other countries such as the United States of America and the United Kingdom. The findings showed that the trend are relatively similar but the difference are in the total numbers of cases between them. Based on the findings, it can be concluded that there are still works to be done in order to overcome the numbers of industrial accidents in Malaysia. All parties must have the responsibilities to prevent accidents by adapting to the health and safety practices in the workplace.